2020
DOI: 10.1088/1757-899x/930/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultimate bearing capacity based on empirical method, interpretation of loading pile test and finite element

Abstract: Civil Engineers in designing the ultimate brearing capacity of the pile usually uses several empirical methods. Then usually the loading pile test will be conducted to confirm the ultimate carrying capcity in the field. Based on conditions that often occurs in the field, an empirical method of research is carried out to find out which method is closest to results of the field test. So that in designing the ultimate bearing capacity of the deep foundation will be closer to the field conditions. The empirical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…One of the methods of Mazurkiewicz (1972) assumes that the greatest resistance capacity (ultimate) will be obtained from intersecting loads, including loads that are in the direction of the pole axis for connected load with points from the position of the line to an angle of 45° on the axis load bordering the load. The procedure for determining the ultimate load using this method is as follows [12]:…”
Section: Methodsmentioning
confidence: 99%
“…One of the methods of Mazurkiewicz (1972) assumes that the greatest resistance capacity (ultimate) will be obtained from intersecting loads, including loads that are in the direction of the pole axis for connected load with points from the position of the line to an angle of 45° on the axis load bordering the load. The procedure for determining the ultimate load using this method is as follows [12]:…”
Section: Methodsmentioning
confidence: 99%
“…Also, the pile loading test result was analyzed using the finite element method based on the results of empirical methods and interpretation of the ultimate bearing capacity of the field test. The results of this study showed the finite element approach, Luciono Decourt, and Lastiasih are the closest to producing ultimate bearing capacity using loading pile tests at failure [18]. The data from pile load tests for three different regions in Nasiriyah, southern Iraq was used to determine pile capacity by adopting various interpreting methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…In the second part of the study, the Ozkan-Alku method was developed [24]. In another study, the results of five different pile loading tests carried out in various parts of the Jakarta region were examined with different methods [27]. The method closest to the results of the pile loading test was found to be the Lastiasih and Sidi methods [28].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the results of 22 pile loading tests in three different areas of Nasiriyah were evaluated with analytical methods [35]. Accordingly, Chin-Kondner and Hansen were the methods that gave the highest failure load [21][22][23][24][25][26][27][28][29][30][31][32]. The Decourt, De Beer, and Mazurkiewicz methods gave the closest mean values to the failure load [5,22,26].…”
Section: Introductionmentioning
confidence: 99%